Exosomal miR-92b-3p Promotes Chemoresistance of Small Cell Lung Cancer Through the PTEN/AKT Pathway - Li, Ming; Shan, Wulin; Hua, Yan; Chao, Fengmei; Cui, Yayun; Lv, Lei; Dou, Xiaoyan; Bian, Xing; Zou, Jinglu; Li, Hong; Lin, Wenchu (Frontiers in Cell and Developmental Biology, 2021)
Resistance to first-line chemotherapy drugs has become an obstacle to improving the clinical prognosis outcome of patients with small cell lung cancer (SCLC). Exosomal miRNAs have been found shown to play pro- and anti-chemoresistant roles in different various cancers, but their role in SCLC chemoresistance has never been explored. In this study, we observed that the expression of exosomal miR-92b-3p was significantly increased in patients who developed chemoresistance. Luciferase reporter analysis confirmed that PTEN was a target gene of miR-92b-3p. The PTEN/AKT regulatory network was involved inrelated to miR-92b-3p-mediated cell migration and chemoresistance in vitro and in vivo in SCLC. Importantly, exosomes isolated from the conditioned medium of SBC-3 cells overexpressing miR-92b-3p could promote SCLC chemoresistance and cell migration. Furthermore, we found that plasma miR-92b-3p levels were significantly higher in patients with chemoresistant SCLC than in those with chemosensitive SCLC, but the levels were downregulated in patients who achieved remission. Kaplan-Meier analysis showed that SCLC patients with high miR-92b-3p expression were associated with shorter progression-free survival. Overall, our results suggested that exosomal miR-92b-3p is a potential dynamic biomarker to monitor chemoresistance in SCLC and represents a promising therapeutic target for chemoresistant SCLC.